KOMUNITAS BURUNG DI DELAPAN TIPE HABITAT DL PULAU SIBERUT, INDONESIA - Adhikerand, Asep S. (BERITA BIOLOGI, 1997)
The recent studies were carried out in June-July 1994,And aimed at investigating the distribution of the avifauna in eight main habitat types of Siberut Island.These habitat types were primary dipterocarp forests,primary mixed forests,secondary forests, swamp forests,mangroves, and coastal forests.It appeared that the habitat types tended to determine the bird communities living in the habitats,suggesting that the distribution of bird communities is related to the resources available within the habitats.The results indicate that the conservation measures of avifauna in this island would be better focused on the conservation of their habitats.